RACE ALGORITHM: ONLINE-MARKETING MODEL PLATFORM - Inessa Penkova; Irina Glazkova (Вестник Северо-Кавказского федерального университета)
The article is aimed at revealing the features of the RACE-model as a model platform for optimizing the online marketing effectiveness. Achieving this goal requires solving two tasks. Firstly, the prerequisitesfor the appearance and analysis of the distinctive key elements of the step-by-step algorithm of the RACE model are considered. Secondly, the features of the of the company's Internet marketing strategy implementation sequence basing on the RACE-model are revealed. The RACE model is the source for planning, covering all contacts with customers and using critical thinking to develop an individual, flexible and strategic approach to the special needs of the business. The distinctive key elements of the RACE algorithm can be covered with its progressive implementation, which includes Reach, Act, Convert and Engage. The peculiarities of the company's Internet marketing strategy implementation based on the RACE-model are the following. It is designed to create the action plans using integrated communications and it is aimed at attracting and convincing customers basing on understanding their needs and analytics. The key concepts of the strategic plan are summarized during its implementation.